2019
DOI: 10.14569/ijacsa.2019.0100631
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of the University Information Systems: Case of Moroccan Universities

Abstract: The purpose of this paper is to develop a conceptual model of university information systems performance measurement. To do this resorted to the choice of 3E-3P model. This model proposes a development under the spectrum of the systemic approach. The objective is to provide a tool to decisionmakers in order to understand the dynamics of performance measurement. The model is based on a logic of decomposition of the global performance into three partial performances. The measurement is carried out at each pillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In this regard, it is obvious that any company must pay particular attention to this part of the flows which are in reality only the consequences of the physical and information flows of a supply chain. In fact the overall performance of companies is linked with their financial performance [2], [3], which make the control of financial flows very important. That said, research has shown that these financial flows are usually undergoing a disruption, referred to as cash flow bullwhip (CFB), and which is observed in almost all supply chains [4].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it is obvious that any company must pay particular attention to this part of the flows which are in reality only the consequences of the physical and information flows of a supply chain. In fact the overall performance of companies is linked with their financial performance [2], [3], which make the control of financial flows very important. That said, research has shown that these financial flows are usually undergoing a disruption, referred to as cash flow bullwhip (CFB), and which is observed in almost all supply chains [4].…”
Section: Introductionmentioning
confidence: 99%